Adherence to Patient Identification Procedures Among Healthcare Professionals in an Indonesian Hospital: A Cross-Sectional Study - Sri Gunarni; Suci Noor Hayati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Accurate patient identification is essential for preventing wrong-patient errors during diagnostic, therapeutic, and administrative procedures. Despite established hospital safety protocols, adherence to identification procedures may remain inconsistent across healthcare professions. Objective: This study examined adherence to standardized patient identification procedures among healthcare professionals at Pasundan Hospital. Methods: A descriptive cross-sectional study was conducted involving 41 healthcare professionals selected through simple random sampling. Adherence was assessed using an observation checklist based on the hospital’s patient identification procedures. Each participant was observed on three separate occasions. Data were summarized using frequencies and percentages. Results: Of the 41 participants, 36 (87.8%) were categorized as adherent and 5 (12.2%) as partially adherent. Physicians demonstrated the lowest adherence, with 11 of 16 physicians (68.8%) meeting the required standard. All nurses and other participating healthcare professional groups were classified as adherent. Conclusion: Adherence to patient identification procedures was generally high but remained below the hospital’s expected standard. Profession-specific audit, feedback, and reinforcement strategies are needed, particularly for physicians, to promote consistent implementation of identification procedures